Feministična literarna veda v slovenskem akademskem prostoru - Mihurko Poniž, Katja (Slavistična revija, 2013)
This article shows how approaches that may be defined as women's literary studies have developed in the context of the academy in Slovenia. It examines key works in the field and the inclusion of materials from women's literary studies in academic programs of Slovene literature and literary theory, as well as how baccalaureate, M.A., and Ph.D. theses reflect on the materials. Research achievements and projects focusing on women authors and portrayals and representations of femininity are also reviewed.
Keywords: feminism; feminist literary studies; feminizem; gender studies; Slovene literary studies; Slovene literature; Slovene women writers; slovenska književnost; slovenska literarna veda; slovenske pisateljice; študije spolov